Maximizing sprint performance among adolescent sprinters: a controlled evaluation of functional, traditional, and combined training approaches - Liu, Xiaohuan; Shao, Yongjing; Saha, Sohom; Zhao, Zijian; Karmakar, Debajit (Frontiers in Public Health, 2025)
BackgroundSprint performance plays a crucial role in competitive sports, particularly among adolescent athletes. Training methodologies such as Functional Training (FT), Traditional Training (TT), and a Combined Training (CT) approach have been widely implemented to improve sprinting ability, agility, and coordination. However, the comparative effectiveness of these methods remains inconclusive. This study aims to evaluate the differential impact of FT, TT, and CT on key physiological and skill-related performance variables in adolescent sprinters.MethodsA total of 52 national-level adolescent sprinters (aged 15–18 years) were randomly assigned to four groups: Functional Training Group (FTG, n = 13), Traditional Training Group (TTG, n = 13), Combined Training Group (CTG, n = 13), and Control Group (CG, n = 13). The intervention lasted for 8 weeks, with training sessions conducted 6 days a week. Sprint performance, agility, coordination, VO₂ max, muscular strength, and body fat percentage were assessed pre- and post-intervention. A repeated-measures ANOVA was used to analyze within- and between-group differences, with significance set at p < 0.05.ResultsCombined Training Group demonstrated the most significant improvements across all performance variables, including VO₂ max (+4.32%), muscular strength (+8.93%), and sprinting ability (−4.71%). FTG showed substantial gains in agility (−2.16%) and coordination (+4.40%), whereas TTG exhibited moderate improvements in strength (+1.43%) and sprint time (−2.18%). The CG group showed no significant changes. Statistical analysis confirmed a significant main effect of training interventions (F = 72.34, p < 0.001, η2p = 0.81), highlighting the superior efficacy of CTG.DiscussionThe findings suggest that a combined approach integrating FT and TT yields optimal improvements in sprint performance by enhancing both neuromuscular coordination and force production. While FT alone is effective in refining agility and coordination, TT primarily contributes to strength gains. The absence of structured training in the CG reinforces the necessity of targeted interventions for performance enhancement. These results provide valuable insights for coaches and sports scientists in designing sprint training programs for adolescent athletes. Future studies could explore the long-term effects of combined FT and TT interventions across different age groups and genders to assess their generalizability.